The Interaction of Reservoir Properties and Microwave Heating- An Experimental and Numerical Modelling Study of Enhanced Gas Recovery (EGR) - Wang, H.; Rezaee, M. Reza; Saeedi, Ali (Elsevier, 2015)
The application of microwave heating in improving the production of natural resources has been studied by many researchers. It is more widely studied in heavy oil recovery by decreasing the viscosity of oil, in drilling to decrease the rock strength and in mineral processing. However, the application of microwave heating in improving gas production is neglected. The present study focused on the interaction of the properties of sandstone electromagnetic wave, computation of the electric field distribution and temperature distribution and how microwave heating leads to an enhanced permeability and an improved gas production. The properties of samples, both petrographic and petrophysical data were measured in the lab and analysed for the purpose of providing data to numerical model. Numerical modelling method is used to model the microwave heating in lab scale and in field scale. The distributions of electric field and temperatures were computed with different sample properties input to study the effects of these properties on microwave heating. It is found that the dielectric properties have impacts on both electric field distribution and temperature distribution while the electrical conductivity affects the temperature distribution only in the present numerical models. A reservoir simulator was used to model how the heating of formation affects the reservoir. Two models were coupled to simulate the formation heating; the input of this model was from the output of the FEM Modelling. The relative permeability and gas relative permeability are plotted to illustrate the effectiveness of EGR assisted by microwave heating. In conclusion, the microwave heating can enhance the relative permeability of gas and remove the water efficiently.